1.5 T MR-linac planning study to compare two different strategies of rectal boost irradiation - Pierluigi Bonomo; Monica Lo Russo; Marcel Nachbar; Simon Boeke; Sergios Gatidis; Daniel Zips; Daniela Thorwarth; Cihan Gani (Clinical and Translational Radiation Oncology, 2021)
Purpose: To compare treatment plans of two different rectal boost strategies: up-front versus adaptive boost at the 1.5 T MR-Linac. Methods: Patients with locally advanced rectal cancer (LARC) underwent standard neoadjuvant radiochemotherapy with 50.4 Gy in 28 fractions. T2-weighted MRI prior and after the treatment session were acquired to contour gross tumor volumes (GTVs) and organs at risk (OARs). The datasets were used to simulate four different boost strategies (all with 15 Gy/5 fractions in addition to 50.4 Gy): up-front boost (5 daily fractions in the first week of treatment) and an adaptive boost (one boost fraction per week). Both strategies were planned using standard and reduced PTV margins. Intra-fraction motion was assessed by pre- and post-treatment MRI-based contours. Results: Five patients were included and a total of 44 MRI sets were evaluated. The median PTV volumes of the adaptive boost were significantly smaller than for the up-front boost (81.4 cm3 vs 44.4 cm3 for PTV with standard margins; 31.2 cm3 vs 15 cm3 for PTV with reduced margins; p = 0.031). With reduced margins the rectum was significantly better spared with an adaptive boost rather than with an up-front boost: V60Gy and V65Gy were 41.2% and 24.8% compared with 59% and 29.9%, respectively (p = 0.031). Median GTV intra-fractional motion was 2 mm (range 0–8 mm). Conclusions: The data suggest that the adaptive boost strategy exploiting tumor-shrinkage and reduced margin might result in better sparing of rectum and anal canal. Individual margin assessment, motion management and real-time adaptive radiotherapy appear attractive applications of the 1.5 T MR-Linac for further testing of individualized and safe dose escalation in patients with rectal cancer.